A novel mixed matrix membrane framework for ultrafast cation sieving. Issue 48 (12th May 2020) - Ran, Jin; Wu, Yuying; Huang, Qiang; Pan, Ting; Chu, Chengquan; Cui, Peng; Zhang, Pengpeng; Sheng, Fangmeng; Ge, Liang; Xu, Tongwen
Abstract : This work reported a new mixed matrix membrane architecture for ultrafast cation sieving. Abstract : This work reported a new mixed matrix membrane architecture. Within this structure, cross-linked sulfonated polymers uniformly distributed into the two dimensional channels stacked by graphene oxide sheets. The resulting membranes show ultrafast perm-selectivity towards mono/multiple-valence cations.